Risk Factors for Postischemic Stroke Epilepsy in Young Adults: A Nationwide Population-Based Study in Taiwan - Do, Phuong Thao; Chen, Li-Ying; Chan, Lung; Hu, Chaur-Jong; Chien, Li-Nien (Frontiers in Neurology, 2022)
Background: The incidence of ischemic stroke has been increasing in the young population over the past 20 years. Poststroke epilepsy (PSE) is a common complication after stroke. However, few population-based studies with sufficient follow-up have investigated on factors associated with PSE in young stroke survivors. Accordingly, this study aimed to determine the long-term incidence and risk factors for PSE young adults. Methods: This cohort study was conducted using data from the Taiwan National Health Insurance Research Database (NHIRD) from 2002 to 2018. All patients aged between 19 and 44 years and diagnosed with ischemic stroke from 2002 to 2015 were retrospectively enrolled with a follow-up of at least three years. Multivariable Cox regression models were performed to identify predictors of PSE, including patients’ demographics, baseline conditions, stroke severity, etiologies, comorbidities, and unhealthy behaviors. Results: Among 6512 ischemic stroke patients, 402 cases (6.2%) developed PSE who were with a mean follow-up period of 8.3 years (SD= 4.3 years). Stroke severity and characteristics were associated with PSE, including National Institutes of Health Stroke Scale (NIHSS) score ≥10 (aHR, 1.98; 95% CI, 1.50–2.61), seizure at first stroke admission [adjusted hazard ratio (aHR), 57.39; 95% confidence interval (CI), 43.02–76.55], length of hospital stay ≥14 days (aHR, 1.60; 95% CI, 1.26–2.02), recurrent stroke (aHR, 2.32; 95% CI, 1.85–2.90), aphasia (aHR, 1.77; 95% CI, 1.20–2.60), and malignancy (aHR, 2.05; 95% CI, 1.30–3.24). Furthermore, stroke patients with drug abuse were 2.90 times more likely to develop PSE than those without (aHR, 2.90; 95% CI, 1.53–5.50). By contrast, statin use (aHR, 0.62; 95% CI, 0.48–0.80) was associated with a lower risk of PSE. Conclusions: Stroke severity, some characteristics, malignancy and drug abuse were associated increased risk of PSE and statin use may protect PSE in young adults. Reducing the severity of stroke, statin use and controlling unhealthy behaviors might be able to decrease the development of PSE. Since PSE is associated with poor outcome, early identification or intervention of PSE based on the risk factors might reduce the harmful effects of PSE.